Banking Performance under the Lens of Earnings Management: A Theoretical and Bibliometric Systematic Review - Nyayu Khalilah Putri; Mohamad Adam; Isnurhadi Isnurhadi; Muizzuddin Muizzuddin (Bulletin of Social Studies and Community Development, 2026)
This study conducts a systematic literature review (SLR) combined with bibliometric analysis to examine earnings management (EM) practices in the banking sector and their implications for financial performance. Following the PRISMA guidelines, the methodology employed a rigorous search strategy using specific keyword combinations, including "earnings management" and "bank", across the ScienceDirect and Scopus databases to capture relevant literature published between 2011 and 2024. Strict inclusion criteria were applied, restricting the final sample to peer-reviewed academic journal articles written in English that explicitly focused on commercial banking institutions, thereby excluding conference proceedings, book chapters, and studies on non-financial firms. This selection process yielded a final core sample of 520 articles for bibliometric mapping. The synthesis identifies key themes, including the influence of governance mechanisms, macroprudential frameworks, discretionary loan loss provisioning, and emerging issues such as digital transformation and Environmental, Social, and Governance (ESG) integration. Findings reveal that bank EM serves as both a strategic response to regulatory and market pressures and a signaling tool to maintain investor confidence. However, it often undermines transparency in reporting. Theoretically, this review extends Positive Accounting Theory by incorporating sustainability considerations and refines Signaling Theory by highlighting potential distortions in information asymmetry when disclosure quality is weak. Crucially, the conclusions offer vital policy implications for regulatory bodies. Policymakers must mandate standardized ESG-based reporting frameworks and enforce stricter oversight on discretionary loan loss provisions to curtail opportunistic accounting behavior. Additionally, macroprudential authorities should synchronize banking governance reforms with international transparency standards to insulate global financial markets from systemic risks, thereby ensuring long-term bank stability and protecting stakeholder trust in highly volatile economic environments. Keywords:  Systematic literature review, Earnings management, Bank performance.